'too beautiful': useless art and the queerly optimistic Make Your Own Brainard Project. (31st March 2021) - Cran, Rona
Abstract: This article offers an account of the British Academy-funded Make Your Own Brainard project, which has put the work of New York School artist and poet Joe Brainard into dialogue with digital media and digital media users via an interactive website: www.makeyourownbrainard.com . The project has created a digital corpus of previous un-exhibited paper fragments (hi-res, 2d images) which were intended for use in Brainard's collages and were discovered among his possessions a number of years after his death. It has enabled users to create their own collages out of the fragments, either digitally or by downloading and printing them for manual assemblage, via a freely accessible bespoke website and app. In doing so the project provides a model for the social and academic significance of user-driven, non-hierarchical, non-monetized artistic activities, and emphasizes the value of enabling and promoting the practical, emotional, and inspirational aspects of making, sharing, and talking about art, rather than inertly observing it. It also argues that the project calls for a reassessment of value judgments regarding 'fun' or even 'useless' art, and suggests that in its queer optimism it raises important questions about existing hegemonic narratives surrounding academic impact, funding for the arts, and the digital humanities.